Integration of An Optimized E-Shaped Patch Antenna into Laptop Structure for Bluetooth and Notched-UWB Standards using Optimization Techniques - Montaser, A M; Mahmoud, K R; Elmikati, H A (Applied Computational Electromagnetics Society journal, 2012)
In this article, an optimized E-shaped patch antenna for Bluetooth (2.4 - 2.484 GHz) and UWB (3.1- 10.6 GHz) applications with WLAN (5.15 - 5.825 GHz) band-notched characteristics is proposed. The dimensions of the E-shaped structure in addition to the position of the slotted C-shape in the ground plane are optimized using recent optimization techniques such as modified particle swarm optimization (MPSO), bacterial swarm optimization (BSO), and central force optimization (CFO). The optimization algorithms were implemented using MATLAB-software and linked to the CST Microwave Studio Suite® version 2011 to simulate the antenna. Next, the effects of the laptop structure on the antenna radiation characteristics are considered. To validate the results, the antenna structures are simulated by the finite difference time domain method (FDTD).